Numerical solutions of quasi-one-dimensional subsonics-supersonic nozzle flows using maccormack's technique - Thian Tze Kwang, 1991-; Norsarahaida Saidina Amin, supervisor; Fakulti Sains (2015)
Project Paper (Sarjana Muda Sains serta Pendidikan (Matematik)) - Universiti Teknologi Malaysia, 2015